New Emigration and Portuguese Society: Transnationalism and Return - Peixoto, João (2019)
This chapter addresses the theme of transnationalism and return in recent Portuguese emigration, namely the flows that occurred after the turn of the century. It starts with a brief theoretical overview on those topics, which constitute two relatively neglected characteristics of Portuguese emigration. Next, based on a survey carried out in 2014–2015 to more than 6000 recent emigrants, it reveals some of the links that they maintain with their home country, as well as their plans for the future, which include settlement in the destination country, return and re-emigration. Lastly, it examines data on returning emigrants – especially those that returned between 2001 and 2011 – extracted from the 2011 Census. The evidence reveals a significant number of returns, including individuals at both working and retirement ages and at all skill levels, thus exposing the unexpected complexity of movements. The results are based on the research project “Back to the future: new emigration and links with Portuguese society” (REMIGR), which aimed to ascertain the extent and characteristics of the new emigration wave. The project included an overview of emigration and return to and from all regions of the world, as well as case studies in UK, France, Luxembourg, Angola, Mozambique and Brazil.